2020
DOI: 10.1016/j.landurbplan.2019.103728
|View full text |Cite
|
Sign up to set email alerts
|

A step towards understanding the relationship between species diversity and psychological restoration of visitors in urban green spaces using landscape heterogeneity

Abstract: Studies have demonstrated a relationship between plant species diversity within urban green spaces (UGS) and psychological restoration of visitors. However, the majority of "non ecologist" visitors are not able to perceive all the different plant species present within UGS. More work is thus needed to explore and better understand the underlying processes of this relationship. Recent studies have suggested that "non ecologist" visitors are able to perceive landscape heterogeneity within UGS, which is related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 56 publications
1
21
0
1
Order By: Relevance
“…A large proportion of the selected studies focus on chemicals present in green spaces through dust, in the soil or in bathing or recreational water accessible in these spaces, that may be risk factors for cancer. In opposition, very few studies adopt a salutogenic perspective considering UGSs as a determinant of health for the individuals who use them [ 10 ] and whose characteristics in terms of layout, plant species [ 69 ], configuration or accessibility may have an influence on the individual and social behaviors of populations [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of the selected studies focus on chemicals present in green spaces through dust, in the soil or in bathing or recreational water accessible in these spaces, that may be risk factors for cancer. In opposition, very few studies adopt a salutogenic perspective considering UGSs as a determinant of health for the individuals who use them [ 10 ] and whose characteristics in terms of layout, plant species [ 69 ], configuration or accessibility may have an influence on the individual and social behaviors of populations [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived biodiversity is measured by asking people for their individual assessment of the species identity or richness in an environment through self-report questionnaires (Fuller et al, 2007;Dallimer et al, 2012;Marselle et al, 2016;Southon et al, 2018;Cameron et al, 2020). Perceived biodiversity has stronger correlations with well-being than actual biodiversity (Dallimer et al, 2012;Cameron et al, 2020;Meyer-Grandbastien et al, 2020). However, the proxy measure of perceived biodiversity cannot replace a measure of actual biodiversity (Hoyle, 2020).…”
Section: Fig 2 Measurement Of Actual and Perceived Biodiversitymentioning
confidence: 99%
“…However, the proxy measure of perceived biodiversity cannot replace a measure of actual biodiversity (Hoyle, 2020). While perceived biodiversity assessments have been shown to be correlated with actual biodiversity measures (Fuller et al, 2007;Southon et al, 2018;Cameron et al, 2020;Meyer-Grandbastien et al, 2020), other studies have found no relationship between the two measures (Dallimer et al, 2012;Shwartz et al, 2014). Perceived biodiversity assessments may over or underestimate the amount of actual biodiversity in a location (Shwartz et al, 2014).…”
Section: Fig 2 Measurement Of Actual and Perceived Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…A. Grabar (see [3] to learn more about Grabar's school or restoration), art theorist and historian I. Glazov [4] are particularly significant for the training of future restorers. Important conclusions were made by contemporary urban environmentalists A. Meyer-Grandbastien, F. Burel, E. Hellier and B. Bergerot [5].…”
Section: Literature Overviewmentioning
confidence: 99%